INVESTIGATION OF THE PROCESS OF SEPARATION OF HARD-TO-DIVIDE WEEDS FROM SEEDS OF PERENNIAL GRASSES - Ковалишин, С. Й.; Дадак, В. О.; Панцир, Ю. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
It is impossible to obtain high yields of cereal grasses without a sufficient quantity of high-quality seeds obtained in the process of post-harvest processing. The presented work is devoted to the study of the process of seed separation of perennial grasses on a pneumoelectric separator. It is difficult to obtain seed material of perennial grasses of high quality in many cases, since it contains a large amount of hard-to-divide impurities and biologically deficient, empty seed. It highlights the main problems of their post-harvest processing. The multifactorial experiment has determined the influence of regulated parameters - the magnitude of the supply of seeds to the channel of the pneumatic separator, the rate of air flow in it and the intensity of the electric field to the quality of the dispersed seed material of the ryegrass. The optimum values of the regulated parameters of pneumatic electro-separation are substantiated, in which the content of heavy separating admixture of weeds in the seed mixture of pasture grasses is the smallest. It is proved that the use in the technological line of seed preparation of perennial grasses of the pneumatic electric separator allows to ensure the quality of the seed material in accordance with the requirements of the existing standards